2020
DOI: 10.1108/jed-11-2019-0062
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure development and industrial sector productivity in Sub-Saharan Africa

Abstract: PurposeThe purpose of this study is to examine whether the state of infrastructure development in Sub-Saharan Africa actually stimulates industrial sector productivity, using a panel data set of 17 countries spanning from 2003 to 2018.Design/methodology/approachThe study used panel least square estimation technique to examine the relationship between the variables.FindingsThe result of the study indicates that the major factor that influences industrial sector productivity in Sub-Saharan Africa is their quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…Finally, financial development is positive and significant in both DOLS and FMOLS models showing the effectiveness of the financial sector in mobilizing funds from the surplus sectors and channeling it to the manufacturing sector, and it supports the findings of Azolibe and Okonkwo (2020); Ogar et al (2014) and Elijah (2018). But excluding high-income countries, it is insignificant in influencing manufacturing sector growth.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Finally, financial development is positive and significant in both DOLS and FMOLS models showing the effectiveness of the financial sector in mobilizing funds from the surplus sectors and channeling it to the manufacturing sector, and it supports the findings of Azolibe and Okonkwo (2020); Ogar et al (2014) and Elijah (2018). But excluding high-income countries, it is insignificant in influencing manufacturing sector growth.…”
Section: Analysis and Discussion Of Resultssupporting
confidence: 78%
“…Financial development is expected to have a positive relationship with the manufacturing sector growth. The studies of Azolibe and Okonkwo (2020); Ogar et al (2014), and Elijah (2018) confirmed a positive relationship between domestic credit to the private sector and the manufacturing sector growth.…”
Section: Data Sources and Definition Of The Variablesmentioning
confidence: 94%
“…Regarding the measurement of infrastructure quality, we follow Kodongo and Ojah (2016), Azolibe and Okonkwo (2020) and approximate it by the African Infrastructure Development Index (AIDI) of the African Development Bank. Available for all 54 African countries over the period 2000-2018, the AIDI is a composite index which monitors the status and progress of infrastructure development across the African continent.…”
Section: Data and Measurementsmentioning
confidence: 99%
“…For example, despite the improvements in electricity access improved from 31% in 2003 to 36.5%, 50% and 51% in 2008, 2013 and 2018, respectively, scholars note with concern the poor quality electricity supply, and an uneven progress in the sub-regions of SSA. Statistics show that whereas only eight countries (Gabon, Mauritius, Reunion, Seychelles, Swaziland, South Africa, Cape Verde and Ghana) had an access rate above 80 per cent in 2016, the majority of countries had a rate below 50 per cent with some operating at a rate below 25 per cent, frequent power outages that on average happen every after four days notwithstanding (Azolibe & Okonkwo, 2020 ; Scott, 2015 ). It should be recalled that though Africa is home to almost a fifth of the world's population, it accounts for less than 4% of global electricity use, with the majority usage recorded in North Africa, leaving more than half of SSA population (about 600 million) in dark (The Economist, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the exceptions is Azolibe and Okonkwo ( 2020 ) who however focus on a smaller panel of 17 countries of SSA to examine the direct role of infrastructure on the industrial sector productivity. Our interest is the manufacturing sector, as we test several hypotheses on a much larger sample of 30 countries, besides taking into account cross-sectional dependence that has been ignored in the latter study, despite being part and parcel of a panel data characteristic especially among countries that likely experience common shocks say, from deeper integration efforts among them.…”
Section: Introductionmentioning
confidence: 99%